Speech Act Analysis of Marhaban Sermon in Bainai Eve at Kapur Region-Lima Puluh District, West Sumatera Province - Lili Hasmi (Politeknik Negeri Bali, 2020)
Social life needs the means to talk about things like contents, intentions, wish, and speech acts. Speech acts are utterances that contain functional units in communication concerning aspects of the conversation. We need to communicate as crucial as life needs to change. Changes from the initial level, from reversal as an adult to old age. Adulthood is often marked by a marriage period. Marriage is a period of transition from adolescent to family life. The marriage in the Minangkabau tradition, in addition to the recitation of the qab ijab, was also carried out on bainai night. Bainai is an activity for leveling nails using henna or henna plants. The crushed henna or henna is applied to all brides' nails and toenails. It is found that several types of utterances, namely the locus of speech, illocution, and perlocution. Based on the background of the problem, the writer is interested in discussing Marhaban's speech in the bainai night program in Kapur District IX, Lima Puluh Kota Regency. The research was a qualitative study using descriptive methods. The informants in this study were all those who participated in the Marhaban bainai night in Kapur District IX in Lima Puluh Regency who used speech acts. Techniques undertaken went through the following stages. Firstly, analysing of Marhaban's speech at the Bainai night event; secondly, analysing Marhaban's speech at the Bainai Night Event; thirdly, interpreting the use of Marhaban's speech on the Bainai night event; Fourthly, discussing the use of Marhaban's speech at the Bainai night event in Kapur District IX in the Lima Puluh Regency. The results revealed, there are speech acts in Marhaban's speech at the Bainai night event in Kapur District IX in Lima Puluh Regency. Types of speech acts obtained were 41 datum about locus speech acts, 32 datum about illocutionary speech acts, and seven datum of speech acts in perlocution